RNase A Promotes Proliferation of Neuronal Progenitor Cells via an ERK-Dependent Pathway - Liu, Hsin-Yu; Chen, Chiung-Ya; Hung, Yun-Fen; Lin, Hong-Ru; Chao, Hsu-Wen; Shih, Pu-Yun; Chuang, Chi-Ning; Li, Wei-Ping; Huang, Tzyy-Nan; Hsueh, Yi-Ping (Frontiers in Molecular Neuroscience, 2018)
Members of the ribonuclease A (RNase A) superfamily regulate various physiological processes. RNase A, the best-studied member of the RNase A superfamily, is widely expressed in different tissues, including brains. We unexpectedly found that RNase A can trigger proliferation of neuronal progenitor cells (NPC) both in vitro and in vivo. RNase A treatment induced cell proliferation in dissociated neuronal cultures and increased cell mass in neurosphere cultures. BrdU (5-Bromo-2´-Deoxyuridine) labeling confirmed the effect of RNase A on cell proliferation. Those dividing cells were Nestin- and SOX2-positive, suggesting that RNase A triggers NPC proliferation. The proliferation inhibitor Ara-C completely suppressed the effect of RNase A on NPC counts, further supporting that RNase A increases NPC number mainly by promoting proliferation. Moreover, we found that RNase A treatment increased ERK phosphorylation and blockade of the ERK pathway inhibited the effect of RNase A on NPC proliferation. Intracerebroventricular injection of RNase A into mouse brain increased the population of 5-ethynyl-2´-deoxyuridine (EdU) or BrdU-labeled cells in the subventricular zone. Those RNase A-induced NPCs were able to migrate into other brain areas, including hippocampus, amygdala, cortex, striatum and thalamus. In conclusion, our study shows that RNase A promotes proliferation of NPCs via an ERK-dependent pathway and further diversifies the physiological functions of the RNase A family.